USING ENTERPRISE RESOURCE PLANNING (ERP) FOR ENHANCING BUSINESS PROCESSES IN SMALL AND MEDIUM ENTERPRISES (SMEs) - Mimin Nur Aisyah (Universitas Negeri Yogyakarta, 2011)
Increasing number of small medium enterprises (SMEs) is using enterprise resourceplanning (ERP) as they start to recognize the benefits provided to the organisations. Thebenefits include tangible and intangible benefits. They can be identified in the operational,managerial, strategic, organizational, as well as in IT infrastructure dimension. Tosuccessfully implement ERP, organizations should recognize the barriers in attainingexpected benefits, especially people-related issues which are more dominant than thetechnical-related. A combination of IT factors and business factors motivate SMEs to adoptERP. However, several factors characterized in SMEs should be considered in analyzingtheir need for ERP. SMEs must prepare themselves in both technical aspects and humanaspects. It is also very important for SMEs to recognize critical success factors (CSFs) thatcontribute to a successful ERP implementation. CSFs can be used to measure the success atdifferent points in the ERP life cycle.Keywords: Enterprise Resource Planning (ERP), small and medium enterprises (SMEs),critical success factors (CSFs), ERP benefits, and ERP adoption